Wujudkan Peluang Ibu Rumah Tangga Berbisnis Melalui Produk Inovasi Buah - Afidufin; Mohamad Bastomi; Genta Mulya Dhafa; Mu’arifah Cahya Winanti (Jurnal Pengabdian Masyarakat Manage, 2024)
Wonoayu Village has the potential to produce a considerable amount of fruits. Despite having abundant natural resources, the community is still constrained in how to utilize the fruit to be processed into valuable food products other than processed chips which are very common in Malang City. Products that are sold raw have low economic value. For this reason, we conducted counseling on fruit candy processing as an alternative to processed products other than chips by making processed food without preservatives which can be a product that can be sold. Financially independent communities are expected to contribute to advancing the village. The implementation methods used are socialization, education, training, mentoring and evaluation. Based on the results of community service activities, it can be concluded that the implementation of this community service activity went smoothly according to plan. This community service activity is able to make processed candy from fruit without preservatives. In addition, the community can make product packaging and marketing strategies through Instagram, marketplace, and WA Business. Fruit candy becomes a processed product that can be sold and brings profit.